Peri-Traumatic Near-Infrared Light Treatment Attenuates the Severity of Noise-Induced Hearing Loss by Rescuing (Type I) Spiral Ganglion Neurons in Mice - Max Meuser; Susanne Schwitzer; Parisa Faraji; Arne Ernst; Dietmar Basta (Brain Sciences)
Background: Previous studies have shown that multiple post-traumatic irradiations of the cochlea with near-infrared light (NIR) can significantly reduce noise-induced hearing loss. However, a single NIR pre-treatment was shown to have the same effect. Extending the pre-treatment time did not result in any further reduction in hearing loss. The present study investigated whether a combined NIR pre- and post-treatment had an increased effect on hearing preservation. Methods: Frequency-specific auditory brainstem potential thresholds (ABR) were determined in young adult mice. One group (n = 8) underwent NIR irradiation (808 nm, 120 mW, 15 min) of the cochlea, followed by a 30 min noise exposure (5–20 kHz, 115 dB SPL). A post-NIR treatment was administered for 30 min immediately following the noise trauma. After 14 days, hearing loss was determined by ABR measurements. The results were compared with a trauma-only group (n = 8) and an untreated control group (n = 5). Subsequently, the spiral ganglion neuron density was investigated. Results: A peri-traumatic NIR treatment resulted in a significantly lower hearing loss compared to the trauma-only group. Hearing protection in these animals significantly exceeded the effect of an exclusive pre- or post-treatment across all frequencies. A loss of spiral ganglion neurons in the trauma-only group was observed, which was significantly rescued by the peri-traumatic NIR treatment. Conclusions: A single peri-traumatic NIR treatment seems to be the more effective approach for the preservation of hearing thresholds after noise trauma compared to an isolated pre- or post-treatment. One target of the protective effect seems to be the spiral ganglion.